Education on the Importance of Immunization for Children at the Juliana Tanjung Morawa Clinic - Turnip, Meria; Siregar, Wilda Wahyuni; Pardede, Desika Wali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Immunization is an effective preventive measure to protect children from various serious infectious diseases. This activity aims to provide education to the public about the importance of immunization for children at the Juliana Clinic, Tanjung Morawa. This activity involves an educational approach in the form of providing education through counseling, interactive discussions, and distributing information media in the form of leaflets. The target of the activity is 18 parents who have children aged 0–5 years. The results of the activity showed that there was an increase in participants' knowledge regarding the benefits of immunization, the immunization schedule, and the risks that might arise if immunization was not carried out. The level of community participation reached 85%, with a positive response to the material presented. It is hoped that this education can increase parents' awareness of the importance of immunization, so that immunization coverage in this area can increase and create herd immunity. In conclusion, the education program at the Juliana Clinic has had a positive impact in increasing public understanding of immunization and it is hoped that it can continue to be carried out on an ongoing basis.